Industry Payments to Obstetrician–Gynecologists: An Analysis of 2014 Open Payments Data. Issue 2 (February 2016) - Tierney, Nicole M.; Saenz, Cheryl; McHale, Michael; Ward, Kristy; Plaxe, Steven
Abstract : OBJECTIVE: To evaluate publically available, individually identified data regarding industry payments made to obstetrician–gynecologists (ob-gyns) during 2014 posted on the Centers for Medicare & Medicaid Services' Open Payments website for the purposes of encouraging ob-gyns to partake in disclosure of their fiscal relationships to patients and to take an active role in maintaining accuracy of their payment data. METHODS: In this retrospective study, we reviewed the Centers for Medicare & Medicaid Services' Open Payments website for all 2014 nonresearch payments to ob-gyns. We compared payments to ob-gyns with payments to those in other specialties as well as subspecialties within the field of obstetrics and gynecology. Univariate statistical analyses were performed. RESULTS: Payments to ob-gyns totaled 60, 004, 472 (3.3% of the total value transferred in 2014) and went to 29, 783 physician recipients. Fifty percent of these payments were for royalties and licensing. Obstetrics and gynecology ranked seventh in total number of payments made to a single specialty (n=311, 485), and 20th of 35 specialties for highest median payment (140, interquartile range 50–347). Medtronic USA, Inc. was the leading payer to ob-gyns. CONCLUSION: Ob-gyns are listed as having received substantial payments from industry in 2014. Because this information is publically available, we suggest physicians become familiar with payment data and the correction process, keep independent records, and register for updates to most effectively manage perceived, or real, conflicts of interest. Abstract : A significant proportion of 2014 industry payments went to obstetrician–gynecologists; physician awareness of their payments is crucial to the transparency process and to maintaining payment accuracy.